Context of action of Proline Dehydrogenase (ProDH) in the Hypersensitive Response of Arabidopsis - Monteoliva, Mariela Inés (2014)
Background:Proline (Pro) dehydrogenase (ProDH) potentiates the oxidative burst and cell death of the plantHypersensitive Response (HR) by mechanisms not yet elucidated. ProDH converts Pro intoΔ1pyrroline-5-carboxylate(P5C) and can act together with P5C dehydrogenase (P5CDH) to produce Glu, or with P5C reductase (P5CR) toregenerate Pro and thus stimulate the Pro/P5C cycle. To better understand the effects of ProDH in HR, we studiedtheenzymeatthreestagesofthedefenseresponsediffering in their ROS and cell death levels. In addition, wetested if ProDH requires P5CDH to potentiate HR.Results:Control and infected leaves of wild type andp5cdhplants were used to monitor ProDH activity,in vivoPro catabolism, amino acid content, and gene expression. Wild type plants activated ProDH at all HR stages. Theydid not consume Pro during maximal ROS accumulation, and maintained almost basal P5C levels at all conditions.p5cdhmutants activated ProDH as wild type plants. They achieved maximum oxidative burst and cell death levelsproducing normal HR lesions, but evidenced premature defense activation.Conclusion:ProDH activation has different effects on HR. Before the oxidative burst it leads to Pro consumptioninvolving the action of P5CDH. During the oxidative burst, ProDH becomes functionally uncoupled to P5CDH andapparently works with P5CR. The absence of P5CDH does not reduce ROS, cell death, or pathogen resistance, indicatingthis enzyme is not accompanying ProDH in the potentiation of these defense responses. In contrast,p5cdhinfectedplants displayed increased ROS burst and earlier initiation of HR cell death. In turn, our results suggest that ProDH maysustain HR by participating in the Pro/P5C cycle, whose action on HR must be formally evaluated in a future.